LncRNAs Stand as Potent Biomarkers and Therapeutic Targets for Stroke - Fan, Junfen; Saft, Madeline; Sadanandan, Nadia; Gonzales-Portillo, Bella; Park, You Jeong; Sanberg, Paul R.; Borlongan, Cesario V.; Luo, Yumin (Frontiers in Aging Neuroscience, 2020)
Stroke is a major public health problem worldwide with a high burden of neurological disability and mortality. Long noncoding RNAs (lncRNAs) have attracted much attention in the past decades because of their newly discovered roles in pathophysiological processes in many diseases. The abundance of lncRNAs in the nervous system indicates that they may be part of a complex regulatory network governing physiology and pathology of the brain. In particular, lncRNAs have been shown to play pivotal roles in the pathogenesis of stroke. In this article, we provide a review of the multifaceted functions of lncRNAs in the pathogenesis of ischemic stroke and intracerebral hemorrhage, highlighting their promising use as stroke diagnostic biomarkers and therapeutics. To this end, we discuss the potential of stem cells in aiding lncRNA applications in stroke.